KNOWLEDGE, ATTITUDE, AND PRACTICES ABOUT YOUTH-FRIENDLY REPRODUCTIVE HEALTH SERVICES AMONG STUDENTS AT MEDICARE HEALTH PROFESSIONALS COLLEGE, MENGO. A CROSS-SECTIONAL STUDY. - NAMBEJJA, JOSEPHINE CLAIRE; ANYWAR , LYDIA (Student's Journal of Health Research Africa, 2024)
Background The term Youth Friendly Reproductive Health Service (YFRHS) refers to those services that are accessible, acceptable, and appropriate for youths such as contraceptive methods; quality obstetric and Antenatal care for all pregnant women and girls and prevention and management of sexually transmitted infections including HIV. Methodology The study employed a cross-sectional study design where 116 respondents were conveniently sampled and comprised young adults both male and female aged between 18-24 years admitted at Medicare Health Professionals’ College, Mengo. Data analysis was presented in tables and figures. Results The majority 113(97.4%) of the respondents had heard about YFRH services, 44(37.9%) of the respondents heard about HIV counseling and testing, while only 6(5.2%) knew of post-abortion care. 69(59.5%) of the respondents did not agree that discussion about contraceptives promotes immorality. 46(39.7%) felt embarrassed to buy condoms from the shop/ health facility. 61(52.6%) of the respondents did not agree that contraceptives are linked to sterility. The highest number 72(62.1%) had ever visited a health facility for YFRH services in the last 12 months. The majority 39(54.1%) of the respondents had used family planning services, only 1(1.4%) had gone for antenatal care while none had post-abortion care. Conclusion The majority of the respondents were knowledgeable about YFRH services, most heard services were family planning and HIV counseling and testing while the least known were antenatal and post about care services. The majority did not agree that discussion about contraceptives with young people promotes immorality. Most respondents had ever visited a health facility for YFRH services with the majority having used family planning services. Recommendations The Ministry of Health should create more awareness regarding youth services such as STI screening and treatment, antenatal care, and post-abortion care to address the high number of unplanned pregnancies and unsafe abortions present.